Role of EPI-FLAIR in Patients with Acute Stroke: A Comparative Analysis with FLAIR - Meshksar, A.; Villablanca, J.P.; Khan, R.; Carmody, R.; Coull, B.; Nael, K. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Further improvement in acquisition speed is needed, if MR imaging is to compete with CT for evaluation of patients with acute ischemic stroke. The purpose of this study was to evaluate the feasibility of implementing an echo-planar fluid-attenuated inversion recovery (EPI-FLAIR) sequence into an acute MR stroke protocol with potential reduction in scan time and to compare the results with conventional FLAIR images. MATERIALS AND METHODS: Fifty-two patients (28 men and 24 women; age range, 32–96 years) with acute ischemic stroke were prospectively evaluated with an acute stroke MR protocol, which included both conventional FLAIR and EPI-FLAIR imaging with integration of parallel acquisition. The image acquisition time was 52 seconds for EPI-FLAIR and 3 minutes for conventional FLAIR. FLAIR and EPI-FLAIR studies were assessed by 2 observers independently for image quality and conspicuity of hyperintensity in correlation with DWI and were rated as concordant or discordant. Coregistered FLAIR and EPI-FLAIR images were evaluated for signal intensity ratio of the DWI-positive lesion to contralateral normal white matter. RESULTS: An estimated 96% of all FLAIR and EPI-FLAIR studies were rated of diagnostic image quality by both observers, with interobserver agreements of κ = 0.82 and κ = 0.63 for FLAIR and EPI-FLAIR, respectively. In 36 (95%) of 38 patients with acute infarction, FLAIR and EPI-FLAIR were rated concordant regarding DWI lesion. The mean ± standard deviation of the signal intensity ratio values on EPI-FLAIR and FLAIR for DWI-positive lesions were 1.28 ± 0.16 and 1.25 ± 0.17, respectively (P = .47), and demonstrated significant correlation (r = 0.899, z value = 8.677, P < .0001). CONCLUSIONS: In patients with acute stroke, EPI-FLAIR is feasible with comparable qualitative and quantitative results to conventional FLAIR and results in reduced acquisition time. AISacute ischemic strokeGREgradient recalled-echoSDstandard deviationSIRsignal intensity ratio